2013
DOI: 10.1111/cei.12086
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of activated, clonally expanded T helper type 17 cells within the CD4+ T cell population in psoriatic lesions

Abstract: SummaryRecent evidence points to the T helper type 17 (Th17) subset as key in the pathogenesis of psoriasis, but cells of this type in lesions remain to be fully characterized. Here we isolated, enumerated, functionally tested and clonotyped the CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…Th17 cells and IL-17 mRNA expression are increased in the dermis of psoriasis affected skin [11], while IL-17A is found in significantly higher levels in lesional psoriasis as compared with nonlesional skin and healthy controls [12]. Comparison of the CD4 + Th cell population from psoriasis lesions ex vivo against peripheral blood samples from the same patients found over-representation of Th17 cells [13].…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…Th17 cells and IL-17 mRNA expression are increased in the dermis of psoriasis affected skin [11], while IL-17A is found in significantly higher levels in lesional psoriasis as compared with nonlesional skin and healthy controls [12]. Comparison of the CD4 + Th cell population from psoriasis lesions ex vivo against peripheral blood samples from the same patients found over-representation of Th17 cells [13].…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…However, the fact that psoriasis is a Th 1 autoimmune disorder is well known from the first evidence, since 2004. Nevertheless, more recently, several authors have already suggested that Th 1 cells may not be as centrally involved as originally thought …”
Section: Discussionmentioning
confidence: 92%
“…The IL-23/IL-17 axis plays a crucial role in the inflammatory and proliferative pathway of both psoriatic skin and joint tissues [33] . Moreover, IL-17 serum levels in psoriatic patients have been shown to be increased compared to healthy controls [59] and T H 17 cell levels were higher in psoriatic plaques than in controls [60] .…”
Section: The Il-23/il-17 Axismentioning
confidence: 98%